Natural products as new antimitotic compounds for anticancer drug development - Carlos Roberto Koscky Paier; Sarah Sant’Anna Maranhão; Teiliane Rodrigues Carneiro; Lídia Moreira Lima; Danilo Damasceno Rocha; Renan da Silva Santos; Kaio Moraes de Farias; Manoel Odorico de Moraes-Filho; Claudia Pessoa (Clinics, 2018)
Cell cycle control genes are frequently mutated in cancer cells, which usually display higher rates of proliferation than normal cells. Dysregulated mitosis leads to genomic instability, which contributes to tumor progression and aggressiveness. Many drugs that disrupt mitosis have been studied because they induce cell cycle arrest and tumor cell death. These antitumor compounds are referred to as antimitotics. Vinca alkaloids and taxanes are natural products that target microtubules and inhibit mitosis, and their derivatives are among the most commonly used drugs in cancer therapy worldwide. However, severe adverse effects such as neuropathies are frequently observed during treatment with microtubule-targeting agents. Many efforts have been directed at developing improved antimitotics with increased specificity and decreased likelihood of inducing side effects. These new drugs generally target specific components of mitotic regulation that are mainly or exclusively expressed during cell division, such as kinases, motor proteins and multiprotein complexes. Such small molecules are now in preclinical studies and clinical trials, and many are products or derivatives from natural sources. In this review, we focused on the most promising targets for the development of antimitotics and discussed the advantages and disadvantages of these targets. We also highlighted the novel natural antimitotic agents under investigation by our research group, including combretastatins, withanolides and pterocarpans, which show the potential to circumvent the main issues in antimitotic therapy.